2013
DOI: 10.1136/annrheumdis-2013-203804
|View full text |Cite
|
Sign up to set email alerts
|

The population prevalence of symptomatic radiographic foot osteoarthritis in community-dwelling older adults: cross-sectional findings from the Clinical Assessment Study of the Foot

Abstract: ObjectivesTo estimate the population prevalence of symptomatic radiographic osteoarthritis (OA) affecting the 1st metatarsophalangeal joint (MTPJ), 1st and 2nd cuneometatarsal joints (CMJs), navicular first cuneiform joint (NCJ) and talonavicular joint (TNJ) in community-dwelling older adults.Methods9334 adults aged ≥50 years registered with four general practices were mailed a health survey. Responders reporting foot pain within the last 12 months were invited to undergo weight-bearing dorso-plantar and later… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
177
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 164 publications
(184 citation statements)
references
References 37 publications
3
177
2
2
Order By: Relevance
“…Sixty randomly selected radiographs were rescored after 8 weeks (by MM) to assess intrarater reliability and were scored by a second experienced reader (HBM) to determine interrater reliability. As reported previously, reliability for the presence of OA was excellent for intrarater (mean κ = 0.94; mean % exact agreement 99%) and moderate for interrater reliability (mean κ = 0.46; mean % exact agreement 79%) 7.…”
Section: Methodssupporting
confidence: 81%
See 2 more Smart Citations
“…Sixty randomly selected radiographs were rescored after 8 weeks (by MM) to assess intrarater reliability and were scored by a second experienced reader (HBM) to determine interrater reliability. As reported previously, reliability for the presence of OA was excellent for intrarater (mean κ = 0.94; mean % exact agreement 99%) and moderate for interrater reliability (mean κ = 0.46; mean % exact agreement 79%) 7.…”
Section: Methodssupporting
confidence: 81%
“…Responders to the health survey reporting pain in or around the foot within the last year and who consented to further contact were invited to attend a research clinic 12. A flowchart showing the recruitment of participants to the CASF study has been published previously 7.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Summated joint scores for the whole hand, DIP and PIP joints had inter- scorer (MM) using 60 pairs of feet from the CAS-F study (26). For summated OST scores, interobserver ICC (95% CI) was 0.81 (0.69 -0.89), and intra-observer ICC (95% CI) was 0.84 (0.58 -0.94)).…”
Section: P9mentioning
confidence: 99%
“…Analysis after the inclusion of ESR, SJC, TJC and VAS-GH, and removal of DAS28 and DAS28-P, showed that erosions were associated with higher ESR (1.77 (1. 26 …”
Section: Cross Sectional Associations Of Baseline Radiographic Scoresmentioning
confidence: 99%